Topic Continuity in the British Council Kids’ Short Story Little Red Riding Hood - Deliana; Br Sembiring, Franinta Egia D. R; Sembiring, Pemina Br (Universitas Pamulang, 2025)
This study explores topic continuity in the British Council Kids’ adaptation of Little Red Riding Hood, focusing on how cohesive devices contribute to coherence in children’s narrative texts. The main objective is to identify and analyze the use of zero pronouns, definite pronouns, indefinite pronouns, third-person pronouns, and possessive pronouns in maintaining topic continuity throughout the story. Employing a qualitative content analysis, the text was segmented into clauses and each relevant linguistic device was coded and examined. Givón’s (1983) framework was applied to measure referential distance, potential interference, and persistence for each device, providing a comprehensive assessment of topic continuity. The findings reveal that definite and third-person pronouns are the most frequently used cohesive devices, with referents usually introduced within one or two clauses, ensuring strong topic tracking and narrative coherence. Zero anaphora is also present, supporting efficient reference maintenance with minimal distance and manageable interference. Notably, the analysis found no instances of indefinite pronouns, indicating a clear focus on specific references throughout the text. Possessive pronouns further clarify relationships and ownership, enhancing textual cohesion. The results show that referential distance and potential interference are generally low, while persistence varies according to narrative focus, reflecting shifts in character relevance. Overall, the study demonstrates that the narrative employs a range of cohesive strategies to maintain topic continuity, which is essential for supporting comprehension and engagement among young readers. These insights offer valuable implications for educators and material developers in designing accessible and coherent reading resources for early language learners